8x-(2x+5)=5x+(3x-8)

Simple and best practice solution for 8x-(2x+5)=5x+(3x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-(2x+5)=5x+(3x-8) equation:


Simplifying
8x + -1(2x + 5) = 5x + (3x + -8)

Reorder the terms:
8x + -1(5 + 2x) = 5x + (3x + -8)
8x + (5 * -1 + 2x * -1) = 5x + (3x + -8)
8x + (-5 + -2x) = 5x + (3x + -8)

Reorder the terms:
-5 + 8x + -2x = 5x + (3x + -8)

Combine like terms: 8x + -2x = 6x
-5 + 6x = 5x + (3x + -8)

Reorder the terms:
-5 + 6x = 5x + (-8 + 3x)

Remove parenthesis around (-8 + 3x)
-5 + 6x = 5x + -8 + 3x

Reorder the terms:
-5 + 6x = -8 + 5x + 3x

Combine like terms: 5x + 3x = 8x
-5 + 6x = -8 + 8x

Solving
-5 + 6x = -8 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-5 + 6x + -8x = -8 + 8x + -8x

Combine like terms: 6x + -8x = -2x
-5 + -2x = -8 + 8x + -8x

Combine like terms: 8x + -8x = 0
-5 + -2x = -8 + 0
-5 + -2x = -8

Add '5' to each side of the equation.
-5 + 5 + -2x = -8 + 5

Combine like terms: -5 + 5 = 0
0 + -2x = -8 + 5
-2x = -8 + 5

Combine like terms: -8 + 5 = -3
-2x = -3

Divide each side by '-2'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| x-4/​5=7 | | 27x^2-27x-35=0 | | (3/8)/9/11 | | (25-2x)(20-2x)(x)= | | y^2*(2.9-y)-1.25=0 | | 16/4x(4)= | | 3-2x=11+2x | | 24=6*b*(1/2) | | 24=6b/2 | | 2a+1/2=3a-1/4 | | 3x^6+9x^4-30x^2=0 | | 7x+1y=80000 | | (16/81)3/4 | | 2cos^2x+3sinx+3=0 | | Y/-12=-36 | | (1-3i)*(5-2zi)=(2i-3)*(3z+2i) | | 3x-(1/7)x=120 | | 4xsquared-8x= | | 8x+9x=37 | | 5(h+1)+3(h-2)=12 | | (x^3-2x^2)+1=0 | | y^2*(120-y)=1.25 | | 8x+3x=32 | | 7x+3x=-1 | | 120y^2-y^3=1.25 | | 3x+20x=200 | | 9x+2x=105 | | 4x+3x=92 | | ln(x/6)=-6 | | 100=80+x | | 0.25b+0.50=13.75 | | 484=4*5.5 |

Equations solver categories